(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This study aims to identify the metaphorical terms included in the lyrics of Taylor Swift’s album "Evermore." Using the theoretical framework offered by Lakoff and Johnson—which highlights the impact metaphorical language has on listeners’ perception and comprehension—the study focuses on analyzing these metaphorical statements. The results show that Swift uses a wide range of metaphorical terms to describe both universal and particular experiences, which heightens the emotional impact and relatability of her songs. By highlighting the critical role that metaphor plays in modern song lyrics and providing insights into how metaphorical language can elicit strong imagery and emotional resonance in listeners, this study makes significant advancements in the discipline of linguistic pragmatics. Through an in-depth analysis of contemporary music, the research underscores how songwriters skillfully utilize metaphors to convey complex emotions, experiences, and narratives that might be difficult to express through literal language alone. This not only enriches the listeners’ interpretative experience but also enhances their emotional connection to the music.